Varför rappar ingen om Norrland längre? En essä om människan, samhället och naturen i Euskefeurats texter - Andersson, Fredrik; Enbom, Jesper; Nordlund, Christer (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2001)
Between 1982 and 1993 the folk music group Euskefeurat released six LPs and gave numerous live performances. As well as being entertaining they also played an important role as subversive cultural critics of the political and environmental circumstances in the north of Sweden, Norrland. This essay highlights three central themes in the lyric production of Euskefeurat: class conflicts, the relationship between centre and periphery and landscape as an arena for value conflicts. The authors argue that these perspectives are neglected today in Swedish popular culture discourse, where urban art directors and Internet-consultants are more in fashion than workers and small farmers in the countryside. The essay asks a concluding question: can contemporary popular music (as hip-hop) channel cultural expressions that capture regional experiences and dilemmas in Norrland?